Optimalisasi Potensi Desa Durian Tinggung Melalui Peningkatan Terhadap Bidang Pendidikan, Kesehatan, Dan Perekonomian Dalam Kegiatan Kuliah Kerja Nyata (KKN) - Putri Juwita; Lolla Novriana Sari Siregar; Bella Puspita; Izmi Fadillah; Viona Eliza; Muhammad Gilang Anugrah (Hikamatzu | Journal of Multidisciplinary, 2024)
This study aims to optimize the potential of Durian Tinggung village through the Community Service Program (KKN) which focuses on improving education, health and the economy. The methods used are field observation and descriptive, and data collection was carried out by 29 KKN groups during the period from July 15 to August 3, 2024. The programs implemented include the main activities. (1) Literacy program for elementary school students, (2) Making bandrek candy as a local product innovation, (3) Socialization of child protection, (4) Digitalization of marketing through Google Maps for local restaurants and small businesses. The results of the study, the KKN program succeeded in increasing students' literacy awareness, developing local economic potential through product innovation, increasing public understanding of child protection, and expanding the marketing reach of local MSMEs through digital platforms. In conclusion, this KKN program has a positive impact on the development of village potential through education and community empowerment, as well as providing valuable experience for students in applying their knowledge in the community.